Pathophysiological insights: insulin resistance and β-cell dysfunction as early markers of pre-diabetes - Lodha, Niraj (International Journal of Research in Medical Sciences, 2026)
Background: Pre-diabetes represents a critical intermediate state of dysglycaemia where both insulin resistance (IR) and β-cell dysfunction (β-CD) contribute to progression toward type 2 diabetes mellitus (T2DM). Methods: A cross-sectional study was conducted among 300 adults, divided into normal glucose tolerance (GT) (control n being 100), pre-T2DM (n being 120), and T2DM (n being 80) groups. Anthropometric and clinical measurements were documented, and biochemical assays were employed to calculate indices of IR (HOMA-IR, QUICKI, Matsuda index) and β-cell function (β-CF) (HOMA-β, insulinogenic index, disposition index, C-peptide). Logistic regression determined predictors of pre-T2DM, whereas ROC analysis evaluated discriminative efficacy. Results: Participants with pre-T2DM and T2DM had greater BMI, waist circumference, and systolic blood pressure than NGT controls (p<0.001). IR measures exhibited a noteworthy stepwise worsening, characterized by increased HOMA-IR and decreased QUICKI and Matsuda indices (p<0.001). The function of β-cells deteriorated progressively among groups, evidenced by decreased HOMA-β, insulinogenic index, disposition index, and C-peptide levels (p<0.001). Logistic regression indicated that HOMA-IR ≥2.5 (OR being 3.48) and HOMA-β <100% (OR being 2.89) are noteworthy predictors of pre-T2DM. ROC analysis showed that the disposition index (AUC being 0.87) was the best way to tell the difference, better than measures of IR. Conclusion: Both IR and β-CD are evident in pre-T2DM, but β-CD indices, particularly the disposition index, demonstrate superior predictive ability. These findings emphasize the need for early screening using combined indices beyond glucose levels to identify individuals at threat of progression.